The role of tutors in mathematical noticing in an undergraduate quantitative literacy course: Conceptualising the time value of money - Mhakure, D. (South African Journal of Higher Education, 2020)
In the past two decades many studies have been carried out on the tutor-student interactions in higher education courses, particularly in undergraduate courses with the foci on exploring students’ deep learning. However, few studies have focussed on the role of tutors’ in “mathematical noticing” during classroom activities. Therefore, this study using the topic on time value of money seeks to explore the roles tutors play during mathematical noticing when facilitating a Quantitative Literacy undergraduate course. Data was collected from transcriptions of two video-recorded tutorials; documentary analysis from students’ written work; and quantitative analysis of the students’ scores from tests and an examination. The findings show that the conceptual issues that students struggle with during the classroom tutorials, remained unresolved as evidenced from the analyses of the students’ written work from the tests and examination. Further research is required to establish the connections between the tutors’ abilities for mathematical noticing and their mathematical knowledge for teaching.